Situation Report: Bulgaria, 9 June 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Drought Once More Threatens Crops A New Crackdown on Bulgarian Art Critics More on June 2 Festivities Comings and Goings High UN Official Visited Bulgaria Riad [Riyad] to Visit Bulgaria Miscellaneous Ideological Conference at the Bulgarian Ministry of the Interior Bulgarian-Czechoslovak Protocol on Scientific Cooperation Bulgarian-Italian Cooperation Turkey to Buy Additional Bulgarian Products Bulgarian-Greek Protocol Signed